Structural Mechanical Properties of Polyethylene Terephthalate (PET) Concrete Subjected to High Temperature - Beddu S.; Alansare A.J.H.; Itam Z.; Mohamad D.; Zainoodin M.M.; Zailani W.W.A. (Springer Science and Business Media Deutschland GmbH, 2024)
Concrete is the most popular and used as building components around the world. One of the most crucial materialsto form concrete is sand. Due to high volume in urbanization, this lead to mass concrete production. Consequently, the quantities of sand found in nature will reduce over time. On the other hand, large quantities of plastic are produced around the world, and due to daily consumption, most plastic is converted into waste. Using plastic inside concrete is one of the best ways to get rid of waste as well as reducing the amount of sand used in concrete production, which in turn helps to reduce environmental risks and preserve the environment. When designing a mixture of concrete containing plastic, the safety of the building must be considered, as the behavior and effect of plastic on concrete change at high temperatures. This study presents the effect of polyethylene terephthalate (PET) on fresh concrete as well as the mechanical properties of concrete containing PET at normal temperatures and high temperatures when using PET as fine aggregate. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.